"Différant des Autres", Espacements et Temporalités Spectrales - Mailhot, Amélie-Anne (Anthropology of consciousness, 2026)
That night that he agreed to our suggestion that we accompany him outside, for the whole night or until the overflow has passed, M seemed to be in direct contact with all the layers of astronomy, inhabiting all temporalities simultaneously. Outside, lying/sitting on the picnic table, in the pitch-black darkness of the night in the woods, under a few stars, he explained to us why we are still, always, in the Big Bang. He made noises of speed, gestured with his arms; his face was tender and laughing. He wanted us to understand; he used all his senses, smoking cigarette after cigarette. The picnic table we're sitting on was made in a "mental health" day center by the same people who made the bench that I sometimes hang around, inscribed: "Différant des autres", which translate as "Differant from the others." I don't believe, though I'm not certain, that the person who wrote it did so with reference to Derridean différance. But that's the idea that immediately struck me, like a door opening onto the possibilities that haunt the bench, those who made it, those who will sit on it, those who will ignore it, those who do ignore it. This sentence on a bench, which makes an unintentional reference to philosophy, suddenly reveals: power relations, diffractions, gaps, injustices, poetry, beauty, and the unalterable impossibility of sameness. Taking the form of a fragmented narrative, this article proposes an investigation into the atmospheres surrounding lived experiences with people who are said to "live with mental health disorders", proceeding through literary-terrestrial back-and-forths between their breath and the rigidity of our capacity to receive them.